Comparing different timings of tourniquet application in total knee arthroplasty: effects on postoperative pain and bone cement interface - Wenbin Wu; Le Cao; Kai Sun; Hongyi Wang (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aims to elucidate the impact of varying tourniquet application timings on postoperative pain and the bone cement interface following TKA. Method Patients who underwent TKA in our department between March 2021 and July 2023 were included in this study. They were randomly assigned to three groups: Group 1 used tourniquets throughout the operation, Group 2 applied tourniquets before the osteotomy, and Group 3 applied tourniquets after completing the osteotomy. The general epidemiological data, tourniquet pressure and duration, postoperative VAS scores, osteotomy surface preparation, blood loss, transfusion rate, KSS scores, knee flexion deformity, knee and thigh circumference differences, and perioperative complications were analyzed and compared among the three groups. Result There was no significant difference in the general epidemiological data among the three groups. At different times after the operation, VAS scores for the surgical site and tourniquet site were significantly different among the three groups. The three groups had similar osteotomy surface preparation before prosthesis installation. At two weeks, they differed significantly in knee flexion deformity. While the differences in knee circumference were not significant, Group 1 had a significantly larger thigh circumference difference than the other two groups at 24 h. The incidence of skin complications and DVT in Group 1 was significantly higher than that in Group 3. Conclusion The use of tourniquets after osteotomy can lead to a good bone cement interface and reduce postoperative leg pain, swelling, and complication rates.